2004
DOI: 10.1590/s0100-879x2004000900005
|View full text |Cite
|
Sign up to set email alerts
|

Expression of inducible nitric oxide synthase is increased in patients with heart failure due to ischemic disease

Abstract: The objective of the present study was to determine the relationship between nitric oxide synthases (NOS) and heart failure in cardiac tissue from patients with and without cardiac decompensation. Right atrial tissue was excised from patients with coronary artery disease (CAD) and left ventricular ejection fraction (LVEF) <35% (N = 10), and from patients with CAD and LVEF >60% (N = 10) during cardiac surgery. NOS activity was measured by the conversion of L- [H 3 ]-arginine to L-[H 3 ]-citrulline. Gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 36 publications
(40 reference statements)
0
23
0
2
Order By: Relevance
“…Increased iNOS activity has been reported in ventricular tissue from patients with dilated cardiomyopathy (6). Increased iNOS activity has also been found in myocarditis, ischemic heart disease, valvular heart disease, and human cardiac allografts, and iNOS levels have been found to correlate with ventricular contractile dysfunction (8,15,20,22). Mungrue et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased iNOS activity has been reported in ventricular tissue from patients with dilated cardiomyopathy (6). Increased iNOS activity has also been found in myocarditis, ischemic heart disease, valvular heart disease, and human cardiac allografts, and iNOS levels have been found to correlate with ventricular contractile dysfunction (8,15,20,22). Mungrue et al.…”
Section: Introductionmentioning
confidence: 99%
“…Increased iNOS activity has been reported in ventricular tissue from patients with dilated cardiomyopathy (6). Increased iNOS activity has also been found in myocarditis, ischemic heart disease, valvular heart disease, and human cardiac allografts, and iNOS levels have been found to correlate with ventricular contractile dysfunction (8,15,20,22). Mungrue et al (19) reported that chronic cardiac-specific upregulation of iNOS in transgenic mice led to increased production of peroxynitrite, which was associated with cardiac hypertrophy and dilatation.…”
mentioning
confidence: 99%
“…Taking all these findings together, we consider that the interindividual variation in the level of iNOS expression during the initial phase of repetitive I/R injury may be associated with interindividual variation in the severity of ICM in the advanced stage. iNOS is considered to be associated with the grade of myocardial injury caused by ischemia, 19,20 and in the patient with ICM the level of myocardial iNOS is related to functional recovery after revascularization. 26 iNOS is upregulated by I/R injury 27 through myocardial inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The second purpose of the present study was to establish an echocardiographic parameter during the initial stage of repetitive I/R injury in the rats that would predict individual severity of ICM in the advanced stage. In addition, inducible nitric oxide synthase (iNOS) expression in the heart, which is known to upregulated by I/R injury 18 and associated with cardiac dysfunction, 19,20 would also be examined in the initial stage of repetitive I/R induced-ICM, to investigate any association with echocardiographic parameters. 90 mg/kg, xylazine: 10 mg/kg), then orally intubated (16G polyethylene tubing) using an otoscope.…”
mentioning
confidence: 99%
“…The endothelial NOS (eNOS) and the neuronal NOS are constitutively expressed and the inducible NOS (iNOS) is biosynthesized in pathological states such as heart failure [127]. At the level of the vasculature, NO is involved in homeostasis, having vasodilator, antiproliferative and antiplatelet actions, as recently reviewed in ref.…”
Section: Nitric Oxide Synthasementioning
confidence: 99%